2020
DOI: 10.36483/vanvetj.821083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastrointestinal Parasitic Infections in Sheep and Goats of Sandwip Island, Chattogram, Bangladesh

Abstract: Gastrointestinal (GI) parasitic infection is considered a common problem in sheep and goat production in Bangladesh. The current investigation was undertaken to determine the prevalence of GI parasitic infection and its associated risk factors (e.g., age, sex, body condition & deworming status etc.) in sheep and goats of the Sandwip Island, Chattogram, Bangladesh. A total of 330 faecal samples of which 220 sheep and 110 goats were taken using a random sampling method. All the samples were subjected to routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…Approximately 50 million people worldwide and over 180 million are at risk of infection in developed and underdeveloped countries ( Nyindo and Lukambagire, 2015 ). In Bangladesh, about 20% of the human population is directly, and 50% indirectly depends on the livestock sectors ( Bhowmik et al., 2020 ), and these large populations are at high risk due to frequent exposure to livestock animals. In ruminant, Fascioliasis is mainly caused by two major zoonotic trematodes spp., Fasciola hepatica and F. gigantic ( Zainalabidin et al., 2015 ); whereas, human Fascioliasis is currently classified as a plant/food-borne trematode infection, commonly acquired by consuming leafy vegetables where metacercaria was encysted on leaves ( Mas-Coma et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50 million people worldwide and over 180 million are at risk of infection in developed and underdeveloped countries ( Nyindo and Lukambagire, 2015 ). In Bangladesh, about 20% of the human population is directly, and 50% indirectly depends on the livestock sectors ( Bhowmik et al., 2020 ), and these large populations are at high risk due to frequent exposure to livestock animals. In ruminant, Fascioliasis is mainly caused by two major zoonotic trematodes spp., Fasciola hepatica and F. gigantic ( Zainalabidin et al., 2015 ); whereas, human Fascioliasis is currently classified as a plant/food-borne trematode infection, commonly acquired by consuming leafy vegetables where metacercaria was encysted on leaves ( Mas-Coma et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…(8.33%; CPG, 6±0.5) (Table 3). Bhowmik et al (2020) found Eimeria sp. among the small ruminants from Sandwip Island, Chattogram, Bangladesh.…”
Section: Resultsmentioning
confidence: 99%
“…The sheep are commonly raised in various centuries for meat, milk, leather and wool production, which further used and processed for making other miscellaneous local products for the domestic market (Gül and Örnek, 2018). Sheep farming is an important segment of the livestock sector (Bhowmik et al, 2020) and is quite common in the Eastern Anatolia region of Turkey. However, parasitic diseases, which are an important factor in the production and yield losses obtained from this sector, cause great losses in meat, milk, leather and wool production (Der, et al, 1994;Değer and Biçek, 2005;Acıöz, 2019).…”
Section: Introductionmentioning
confidence: 99%